PENGARUH PENGGUNAAN MEDIA GAME EDUCAPLAY TERHADAP PENINGKATAN PEMAHAMAN KONSEP MATERI ENERGI DISEKITAR KITA PADA SISWA KELAS III DI SDN GORDA 2 - Ningrum, Sulistia; Diana Ayu Rostikawati; Sohri Ramadhan Al-Fikri; Ani Purwatisari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Students' understanding of the concept of energy in everyday life is still relatively low, which affects less than optimal learning outcomes. This study aims to test the effectiveness of using Educaplay as an interactive learning medium in improving the understanding of energy concepts in third-grade students at SDN Gorda 2. The research method used a quasi-experimental approach with a two-group pretest–posttest design, where the experimental class received treatment using Educaplay media, while the control class received conventional learning. The research instrument was a multiple-choice test totaling 25 questions given before and after the treatment. Data were analyzed through prerequisite tests and non-parametric tests. The results showed a significant effect of using Educaplay (p < 0.05). The average increase in student understanding in the experimental class reached 58.05%, while in the control class only 35.30%. These findings confirm that the use of Educaplay is effective as an alternative learning strategy. In addition, this study provides practical implications for teachers in selecting innovative and appropriate digital learning media to support the learning process of elementary school students.